The medical student as behavioural psychotherapist. Issue 5962 (12th April 1975) - Stern, R S
Abstract : A group of medical students were randomly selected from a larger group to carry out behaviour therapy under supervision. Ten patients with phobic disorders and two with obsessive-compulsive neurosis were treated, and the results, assessed by ratings of proved reliability, compared favourably with other studies in which psychiatrists or nurses acted as therapists. A questionnaire survey showed that students involved in therapy had a more favourable opinion about this kind of treatment than those receiving only theoretical instruction. The results suggested not only that medical students make good behavioural psychotherapists but also that the subject is a worthwhile training experience which warrants inclusion in the curriculum.